The Experiences and Evaluation of a Complex Intervention for Couples Coping With Stroke - Ramazanu Sheena; Lim Chiang Vico Chung; Välimäki Maritta (United States, 2022)
BACKGROUND: Globally, stroke is a leading cause of death and disability. With a strong sense of filial responsibility, Asian caregivers are committed to caring for their ill family members. In response, the 3H (Head, Heart, Hands) intervention was developed and implemented in Singapore to support couples in their coping after a stroke. The purpose of this study is to explore the experiences of the participants taking part in the 3H intervention and evaluate the intervention after they had participated in it.
METHODS: An interpretive descriptive design was used. Semistructured qualitative interviews were conducted with 7 patients and 7 spousal caregivers. Data were analyzed using conventional content analysis.
RESULTS: The participants' experience was described as one of becoming more prepared to face the storm. The "storm" resulted from a stroke, where the participants were worried and uncertain about their future. After participating in the intervention, the couples' coping processes had improved. They coped by breaking the silence and engaging in conversations, cultivating a sense of support, and conveniently fulfilling their educational needs. It was evaluated that extending the 3H intervention for community nursing is necessary to strengthen the care transition of couples from the hospital to home.
CONCLUSION: New knowledge has been gained that the 3H intervention is useful and may be implemented in a clinical context before a patient's discharge from hospital. As a result of participating in the 3H intervention, effective coping was evident where participants engaged in conversations, cultivated a sense of support, and fulfilled their educational needs. Primary healthcare professionals should pay more attention to the difficulties and needs of this group of people, provide more resources to support them, and improve their quality of life.